Impacts of agricultural producer support on climate and nutrition outcomes with special emphasis on Latin America and the Caribbean - Glauber, Joseph W.; Laborde Debucquet, David; Piñeiro, Valeria (Instituto Interamericano de Cooperación para la Agricultura, 2021)
Despite significant reforms over the past 25 years, the agricultural sector remains highly subsidized. Agricultural producer support is projected to reach almost USD 1.8 trillion in 2030 (FAO/UNDP/UNEP 2021). About 73 percent of this (USD 1.3 trillion) is projected to be in the form of border measures, which affect trade and domestic market prices. The remaining 27 percent (USD 475 billion) is projected to be in the form of fiscal subsidies to agricultural producers. About two thirds of the total producer support (USD 1.2 trillion) is estimated to support crop production while one third (USD 595 billion) is expected to go to livestock producers.